1990
DOI: 10.1128/jb.172.12.7011-7019.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of a bile acid-inducible operon from Eubacterium sp. strain VPI 12708

Abstract: Two bile acid-inducible polypeptides from Eubacterium sp. strain VPI 12708 with molecular weights of 27,000 and approximately 45,000 have previously been shown to be encoded by genes residing on a 2.9-kb EcoRI fragment. We now report the cloning and sequencing of three additional overlapping DNA fragments upstream from this EcoRI fragment. Together, these four fragments contain a large segment of a bile acid-inducible operon which encodes the 27,000- and 45,000-Mr (now shown to be 47,500-Mr) polypeptides and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
84
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 26 publications
1
84
0
Order By: Relevance
“…The baiB gene from Eubacterium sp. strain VPI 12708 is contained in a 2.4-kb chromosomal EcoRI fragment that was initially cloned in E. coli Y1090 by using a Xgtll vector (20). This 2.4-kb fragment was subsequently subcloned in E. coli DH5a by using a pUC19 vector (8).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The baiB gene from Eubacterium sp. strain VPI 12708 is contained in a 2.4-kb chromosomal EcoRI fragment that was initially cloned in E. coli Y1090 by using a Xgtll vector (20). This 2.4-kb fragment was subsequently subcloned in E. coli DH5a by using a pUC19 vector (8).…”
Section: Methodsmentioning
confidence: 99%
“…The genes (baiE and baiF) encoding two other verified bile acid-inducible polypeptides are also included among the six or more open reading frames present in this operon. Most of the enzymes involved in bile acid 7ao-dehydroxylation are thought to be encoded from this operon (20). It has been suggested that the 7-dehydroxylation reaction may provide an ancillary electron acceptor for bacteria capable of expressing this activity (15).…”
mentioning
confidence: 99%
See 3 more Smart Citations